Increasing melanoma incidence in the elderly in North-East Hungary: is this a more serious problem than we thought?. Issue 6 (November 2019) - Janka, Eszter A.; Kékedi, Kriszta; Várvölgyi, Tünde; Gellén, Emese; Kiss, Borbála; Remenyik, Éva; Emri, Gabriella
Abstract : There is a great need for efficient and cost-effective melanoma screening, but this is not yet solved. Epidemiological studies on trends in melanoma incidence by tumour thickness, anatomical site and demographical data can help to improve public health efforts regarding earlier melanoma diagnosis. We aimed to study the trends in the incidence and characteristics of patients and their melanoma in North-East Hungary from 2000 to 2014. Data were obtained from a university hospital-based registry. A total of 1509 cutaneous invasive melanomas of 1464 patients were included in the study. A moderate but significant increase in incidence was observed in the region [average annual percentage change: 3.04 (0.07; 6.11); P = 0.045], with a breakpoint in 2007. From 2001 to 2007, the trend was increasing [APC: 9.84 (3.52; 16.55); P =0.006], but it stalled from 2007 [APC: −2.45 (−5.99; 1.23); P = 0.164]. However, in the age groups over the age of 60 years, where the standardised incidence was the highest, the incidence continued to rise. Furthermore, older age, male sex and trunk or lower extremity localization were found to be associated with thicker melanomas. Our results support that regular screening examination for melanoma would be desirable for people over the age of 60 years. Abstract : Supplemental Digital Content is available in the text.